Análise de Agrupamento da Temperatura do ar no Sul do Brasil entre 1961-2011 - Rosso, Flávia Venturini; Boiaski, Nathalie Tissot; Ferraz, Simone Erotildes Teleginski (Ciência e Natura, 2013)
The economy in the southern Brazil is based on agriculture and livestock sectors which, in turn, depend on the meteorological parameters variability, such as precipitation and temperature. In this study was performed a climatological analysis of the air temperature in the southern Brazil during 1961-2011, using the cluster analysis and thereby providing information about the temperature spatial variability on the region.